Systematic literature review on surgical site preparation in paediatric surgery - Isabella Bielicki; Ulrike Subotic; Julia Anna Bielicki (BMC, 2022)
Abstract Background Surgical site infections (SSIs) in children represent a common and serious postoperative complication. Surgical skin preparation is an essential preventive measure in every surgical procedure. The most commonly used antiseptic agents for surgical skin preparation are chlorhexidine gluconate and iodophors in alcohol-based solutions. In adult patients the use of chlorhexidine-containing antiseptic solutions for preoperative skin preparation has been advocated to reduce SSI rates. Our objective was to conduct a systematic literature review on use of antiseptic agents for surgical skin preparation in children less than 16 years of age. Methods A systematic review of MEDLINE, EMBASE, CINAHL and CENTRAL was performed using both MeSH and free text terms and using the relevant Cochrane filter to identify full text randomized trials (RCTs) and comparative observational studies. Interventions of interest were the choice of main agent in antiseptic solutions (chlorhexidine/povidone-iodine/alcohol) compared with each other or with other antiseptic agents. Primary outcome was the reported rate of surgical site infections. Results In total 8 studies were included in the review; 2 RCTs and 6 observational studies. Observational studies generally did not primarily investigate the association of different antiseptics with subsequent SSI. The identified randomised controlled trials included only 61 children in total, and were of low quality. Consequently, we did not conduct a formal meta-analysis. Since the publication of a comprehensive systematic review of perioperative measures for the prevention of SSI in 2016, no randomized controlled trials comparing antiseptic agents for surgical skin preparation in paediatric surgery have been conducted. Conclusion Robust evidence on the optimal skin antisepsis to reduce SSIs in children is lacking. Direct extrapolation of effects from trials involving adults is not appropriate as physiologic characteristics and risk factors for SSIs differ between adults and children. It is therefore essential to conduct high quality RCT investigating interventions to identify optimal measures to reduce SSI rates in children. Trial registration Prospero registration ( CRD42020166193 ).